Assessment of organochlorine pesticide residues in raw food samples from open markets in two African cities. (December 2016) - Nuapia, Yannick; Chimuka, Luke; Cukrowska, Ewa
Abstract: This study investigates the level of organochlorine pesticides in the raw food from open markets in Kinshasa, Democratic Republic of Congo (DRC), and Johannesburg, South Africa. It assesses the potential health risks associated with the organochlorine pesticide residues. The Quick, Easy, Cheap, Effective, Rugged, and Safe (QuEChERS) method has been developed for sample preparation. A total of 120 food samples (beans, cabbage, beef, and fish) were obtained from the open markets. The mean concentrations of organochlorine pesticides in raw foods collected from the Johannesburg market were significantly higher ( p  < 0.05) than those from the Kinshasa market. DDE recorded the highest mean concentration (253.58 ± 4.78 μg kg −1 ) in beef from Johannesburg, and α-BHC recorded the lowest mean concentration (38.54 ± 7.46 μg kg −1 ) in beans from Kinshasa. The investigation of health risk estimates revealed that the number of organochlorine pesticides exceeded the reference dose in the collected food samples. Highlights: Assessment of organochlorine pesticide residues in raw food samples from open markets in two African cities was performed. Quick, Easy, Cheap, Effective, Rugged and Safe (QuEChERS) method has been developed as sample preparation technique. Health risk estimates were calculated.